Islamic education on line : a case study - Fontaine, Rodrigue Ancelot Harvey (2013)
This paper reports on two interrelated projects related to Islamic education on-line. The first project, entitle The Happy in Islam project, requires students to listen to one Islamic talk on the Internet during the semester and submit an end-of-semester report. The outcomes of this project have generally been positive (Fontaine, 2011). In particular, it promotes critical thinking and spiritual intelligence. Using an action research methodology, the Happy in Islam project is being modified with the help of Mr. Fazrul Ismail from Total Success Sdn Bhd to promote online Islamic education in Malaysian schools. The strategic and operational challenges of transforming an academic project into a sustainable profit-making organization are discussed. The general conclusion is that academics can develop ‘proof-of-concepts’ but that commercial organizations are needed to make the project sustainable over the long-term.